Communication between nodes in backscatter-assisted wireless powered communication network - Jie TAO; Haijiang GE; Minyuan WU; Qike SHAO; Kaikai CHI (Dianxin kexue)
At present, there is almost no design on information transmission between the nodes in wireless powered communication network.The high-throughput information transmission between the nodes in backscatter assisted wireless powered communication network was studied.A scheme was proposed which consisted of backscattering/energy transmission phase and active communication phase.The maximum throughput was modeled as a convex optimization problem.Then, based on the relationship between the total backscatter communication duration and the threshold of node energy capture duration, the problem was decomposed into several sub problems that only need to optimize two backscatter durations.An efficient two-level golden section search algorithm was designed to solve the sub problems, and the optimal solution of the original problem was obtained from the optimal solutions of the sub problems.Simulation results show that, compared with pure active communication scheme and pure backscatter communication scheme, the proposed scheme can effectively improve the throughput.